Molecular Docking and Pharmacokinetic Studies of Moringa oleifera As Angiotensin-Converting Enzyme Inhibitors - Rahmawaty Hasan; Rina Herowati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Hypertension in pregnancy is a vascular disorder that occurs before pregnancy or arises during pregnancy that there were 30% of cases of maternal death. Moringa oleifera's potential to lower blood pressure can be utilized as an alternative antihypertensive during pregnancy, minimizing the risk of preeclampsia. Objective: The purpose of this study was to determine the molecular target of Moringa oleifera is intended to optimize pharmacodynamic activity based on the interaction pattern of the compounds with the ACE inhibitor (PDB ID: 1O86). Methods: Molecular docking is carried out using Autodock 4.0 program (AutoDock Tools). Results: According to the binding energy value and ACE inhibitory interaction, a-Rhamnopyranosyl, b-Sitosterol, and Sinalbin are prospective Moringa oleifera compounds as alternative antihypertensive. These potential compounds can inhibit ACE with binding energy -8.23; -9.27; -9.14 kcal/mol. Pharmacokinetic predictions reported that the potential compounds are absorbed in the intestine and indicates as molecules are tightly bound to plasma proteins and, as well as CYP3A4 and CYP2C9 inhibitors. The prediction of toxicity indicates that the potential compounds are classified as drug-induced acute liver failure with low carcinogens. Conclusion: a-Rhamnopyranosyl, b-Sitosterol and Sinalbin can be suitable lead compounds for synthetic drugs for antihypertensive agents.